Surrounded by bad bosses (and lazy employees) : how to stop struggling, start succeeding, and deal with idiots at work - Erikson, Thomas, 1965- (St. Martin's Essentials, 2021)
"Internationally bestselling author Thomas Erikson has helped changed how the world thinks about behavior using a simple 4-color behavior analysis system. In Surrounded by Bad Bosses he applies that same system to revolutionize the workplace. Everyone has had a bad boss. You might have one right now. You might even be one. Bad bosses are a fact of the workplace, whether they're short-tempered, unclear about expectations, or too disorganized to manage so much as a stapler. But how do you not only survive a difficult boss, but help your career thrive despite them? By identifying your boss's behavior profile you'll be better able to interact with them no matter what the situation. Erikson offers example stories and concrete steps to help you thrive in any work situation. Of course, much as we love to blame our bosses, sometimes management isn't the problem at all. For every bad boss there is also a lazy employee, so Erikson also looks at the issue from a completely different perspective-employees themselves- and explores why some colleagues frequently underachieve, and what you can do to change this. Written with Erikson's signature humor and warmth, Surrounded by Bad Bosses (And Lazy Employees) will help you deal with the most hopeless managers and employees you can imagine-and keep you entertained along the way"--